Nanocomposite particles and methods of making and using same

JP2024515163A5Active Publication Date: 2025-03-06KINNERET ACADEMIC COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023557333
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-03-17
Filing Date
2022-03-02
Publication Date
2025-03-06
Estimated Expiration
2042-03-02

AI Technical Summary

Technical Problem

Plastic waste recycling generates unpleasant odors due to volatile organic compounds (VOCs) and microbial contamination, which are difficult to manage with existing odor masking and absorption technologies.

Method used

The use of poly(ethyleneimine) (PEI) grafted nanoparticles, such as fumed silica, methacrylic silica, aluminum oxide, zinc oxide, zeolite, titanium dioxide, carbon nanotubes, and graphene, to reduce odors by directly attaching PEI to nanoparticle surfaces through sonication with benzoyl peroxide, enhancing odor absorption and dispersion in polymeric materials.

Benefits of technology

The PEI-grafted nanoparticles effectively reduce odors in recycled plastics by improving odor absorption and dispersion, outperforming commercial additives and demonstrating higher efficacy in odor reduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000031_0000
    Figure 00000031_0000
  • Figure 00000031_0001
    Figure 00000031_0001
  • Figure 00000031_0002
    Figure 00000031_0002
Patent Text Reader

Abstract

A population of nanocomposite particles is disclosed that includes nanoparticles and poly(ethyleneimine) (PEI) grafted thereto. In some embodiments, the PEI-coated nanoparticles include at least one member selected from the group consisting of silica nanoparticles, methacrylic silica nanoparticles, aluminum oxide (Al2O3) nanoparticles, ZnO nanoparticles, zeolite nanoparticles, TiO2 nanoparticles, carbon nanotube nanoparticles, and graphene nanoparticles. In some embodiments, there is no intervening layer between the nanoparticles and the PEI. Methods of making and using the nanocomposite particles are also disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (Details of related application) This PCT application claims priority under 35 U.S.C. §119(a) of Israel Application No. 281,582, filed March 17, 2021, which is incorporated by reference herein in its entirety.

[0002] (Acknowledgements) This research was conducted as part of the CIRCLE consortium, which is supported by the Technology Infrastructure Division of the Israel Innovation Authority.

[0003] The present invention is in the field of nanoparticles. [Background technology]

[0004] Global plastic waste production was about 360 million tonnes in 2018 and continues to grow. About 40% of plastic waste is converted into energy, mainly through combustion reactions. Only 15% of plastic waste is recycled. Most of the remaining 45% of plastic waste is sent to landfills.

[0005] Recycling is attractive both economically and environmentally. Demand for plastic packaging is constantly increasing, while "virgin" plastic raw materials are in decline. Recycling of packaging waste has the potential to contribute to a circular economy.

[0006] Unfortunately, plastics recycled from household waste can release over 70 volatile compounds, including aromatics (e.g. limonene). These compounds are commonly referred to as "volatile organic compounds" or "VOCs."

[0007] Volatile compounds (including VOCs) released from plastics are typically characterized / measured by Gas Chromatography-Olfactometry (GC-O). GC-O utilizes gas chromatography analysis to identify compounds responsible for odors that are enhanced by human senses. GC-O provides a correspondence between the molecular structure of odor-active components and human perception. GC-O has established that extrusion during recycling generates new aromas. In GC-O, Gas Chromatography-Mass Spectrometry (GCMS) is complemented by results from human "odor panels" that "sniff" the samples.

[0008] Additionally, microbiologically contaminated organic matter with which plastic waste comes into contact and / or the fillers used in recycling can also be a source of unwanted odors.

[0009] Alternatively or additionally, factors such as light, heat, irradiation etc. may change the chemical and physical properties of the polymer, resulting in the release of odorants.

[0010] In some cases, fragrances are used to mask the unpleasant odors of plastics. In addition, odor-reducing additives have been developed. For example, graphene aerogel (GA) has been developed. GA is thought to absorb VOCs. Summary of the Invention

[0011] A broad aspect of the present invention relates to reducing odor.

[0012] An aspect of some embodiments of the present invention relates to poly(ethyleneimine) (PEI) grafted to nanoparticles. In some embodiments, the grafting is direct, meaning that the nanoparticles are not pretreated with another material before attaching the PEI. According to various exemplary embodiments of the present invention, the nanoparticles include fumed silica (hydrophilic and / or hydrophobic) and / or methacrylic silica and / or aluminum oxide (Al2O3) and / or zinc oxide (ZnO) and / or zeolite and / or titanium dioxide (TiO2) and / or carbon nanotubes and / or graphene and / or carbon black. According to various exemplary embodiments of the present invention, the nanoparticles have an average size of at least 5 nm, at least 10 nm, at least 15 nm, at least 20 nm, at least 30 nm, at least 40 nm, at least 50 nm, at least 60 nm, at least 70 nm, at least 80 nm, at least 90 nm, at least 100 nm, or intermediate or larger. Alternatively or additionally, according to various exemplary embodiments of the present invention, the nanoparticles have an average size of less than 200 nm, less than 100 nm, less than 90 nm, less than 80 nm, less than 70 nm, less than 60 nm, less than 50 nm, less than 40 nm, less than 30 nm, less than 25 nm, less than 20 nm, less than 15 nm, less than 12 nm, less than 10 nm, or less than intermediate sizes.According to various exemplary embodiments of the present invention, the PEI has a molecular weight of at least 600 g / mol, at least 1000 g / mol, at least 5000 g / mol, at least 10,000 g / mol, at least 15,000 g / mol, at least 20,000 g / mol, at least 25,000 g / mol, at least 10,000 g / mol, at least 15,000 g / mol, at least 20,000 g / mol, at least 25,000 g / mol, at least 30,000 g / mol, at least 35,000 g / mol, at least 40,000 g / mol, at least 45,000 g / mol, at least 50,000 g / mol, at least 55,000 g / mol, at least 60,000 g / mol, at least 100,000 g / mol, at least 50,000 g / mol, at least 65,000 g / mol, at least 70,000 g / mol, at least 80,000 g / mol, at least 85,000 g / mol, at least 90,000 g / mol, at least 10 ... 0 g / mol, at least 60,000 g / mol, at least 65,000 g / mol, at least 70,000 g / mol, at least 75,000 g / mol, at least 70,000 g / mol, at least 75,000 g / mol, at least 80,000 g / mol, at least 85,000 g / mol, at least 90,000 g / mol, at least 95,000 g / mol, at least 190,000 g / mol, at least 290,000 g / mol, at least 390,000 g / mol, at least 490,000 g / mol, at least 590,000 g / mol, at least 690,000 g / mol, or intermediate or higher molecular weight. Alternatively or additionally, according to various exemplary embodiments of the present invention, the PEI has a molecular weight of less than 755,000 g / mol, less than 650,000 g / mol, less than 550,000 g / mol, less than 95,000 g / mol, less than 85,000 g / mol, less than 80,000 g / mol, less than 75,000 g / mol, less than 70,000 g / mol, less than 65,000 g / mol, less than 60,000 g / mol, or less than 55,000 g / mol. , less than 50,000 g / mol, less than 45,000 g / mol, less than 40,000 g / mol, less than 35,000 g / mol, less than 30,000 g / mol, less than 25,000 g / mol, less than 20,000 g / mol, less than 15,000 g / mol, less than 10,000 g / mol, less than 5,000 g / mol, less than 4,000 g / mol, less than 4,000 g / mol, less than 1,000 g / mol, or intermediate or lower molecular weight. Alternatively or additionally, according to various exemplary embodiments of the present invention, the PEI is linear or branched.

[0013] Another aspect of some embodiments of the present invention relates to the use of ultrasonic treatment to graft poly(ethyleneimine) (PEI) onto nanoparticles. According to various exemplary embodiments of the present invention, the nanoparticles are as described above. According to various exemplary embodiments of the present invention, the amount of PEI relative to the nanoparticles is at least 0.1%, at least 0.25%, at least 0.5%, at least 1%, at least 2.5%, at least 5%, at least 10%, at least 20%, at least 30%, at least 60%, at least 100%, at least 150%, at least 200%, or at least 300%, or intermediate or higher percentages, on a W / W basis. Alternatively or additionally, according to various exemplary embodiments of the present invention, the amount of PEI relative to the nanoparticles is less than 400%, less than 300%, less than 200%, less than 150%, less than 100%, less than 60%, less than 30%, less than 20%, or less than 10%, or intermediate or lower percentages, on a W / W basis. In some exemplary embodiments of the present invention, the addition of benzoyl peroxide (BP) during ultrasonication contributes to the initiation of grafting of PEI to the nanoparticles. In some embodiments, BP provides free radicals. In some exemplary embodiments of the present invention, the nanoparticles are ultrasonicated in a liquid carrier to form a suspension prior to grafting of PEI. According to various exemplary embodiments of the present invention, the amount of BP relative to the nanoparticles is at least 0.1%, at least 0.25%, at least 0.5%, at least 1%, at least 1.5%, at least 2%, at least 3%, or intermediate or higher percentages on a W / W basis. Alternatively or additionally, according to various exemplary embodiments of the present invention, the amount of BP relative to the nanoparticles is less than 5%, less than 4%, less than 3%, less than 2%, less than 1.5%, less than 1%, less than 0.5%, less than 0.25%, less than 0.15%, or intermediate or lower percentages.

[0014] A further aspect of some embodiments of the present invention relates to the incorporation of PEI-grafted nanoparticles into polymeric materials as described above. In some embodiments, the incorporation occurs during or before the manufacturing process. According to various exemplary embodiments of the present invention, the polymeric materials include virgin and / or recycled materials. In some embodiments, the incorporation of PEI-grafted nanoparticles contributes to reducing odors emanating from the polymeric materials and / or from fillers and / or additives contained therein.

[0015] A further additional aspect of some embodiments of the present invention relates to applying the PEI-grafted nanoparticles to the surface of a product, as described above. In some embodiments, applying the PEI-grafted nanoparticles to the surface of a product contributes to reducing odors emanating from the product.

[0016] It will be appreciated that the various embodiments described above are directed to solving technical problems associated with the production of PEI coated nanoparticles.

[0017] Alternatively or additionally, it will be appreciated that the various aspects described above relate to solving technical problems related to the reduction of odors emanating from various types of products and / or various types of waste products and / or from polymeric materials used in their production and / or from fillers in the polymeric materials and / or from gases.

[0018] In some exemplary embodiments of the present invention, a population of nanocomposite particles is provided that includes (a) hydrophilic fumed silica nanoparticles and (b) poly(ethyleneimine) (PEI) grafted thereto, wherein there is no intervening layer between the nanoparticles and the PEI.

[0019] In some exemplary embodiments of the present invention, a population of nanocomposite particles is provided that includes (a) hydrophobic fumed silica nanoparticles and (b) poly(ethyleneimine) (PEI) grafted thereto.

[0020] In some exemplary embodiments of the present invention, a population of nanocomposite particles is provided that includes (a) methacrylic silica nanoparticles and (b) poly(ethyleneimine) (PEI) grafted thereto.

[0021] In some exemplary embodiments of the present invention, a population of nanocomposite particles is provided that includes (a) aluminum oxide (Al2O3) nanoparticles and (b) poly(ethyleneimine) (PEI) grafted thereto.

[0022] In some exemplary embodiments of the present invention, a population of nanocomposite particles is provided that includes (a) zinc oxide (ZnO) nanoparticles and (b) poly(ethyleneimine) (PEI) grafted thereto.

[0023] In some exemplary embodiments of the present invention, a population of nanocomposite particles is provided that includes (a) zeolite nanoparticles and (b) poly(ethyleneimine) (PEI) grafted thereto.

[0024] In some exemplary embodiments of the present invention, a population of nanocomposite particles is provided that includes (a) titanium dioxide (TiO2) nanoparticles and (b) poly(ethyleneimine) (PEI) grafted thereto.

[0025] In some exemplary embodiments of the present invention, a population of nanocomposite particles is provided that includes (a) carbon nanotube nanoparticles and (b) poly(ethyleneimine) (PEI) grafted thereto.

[0026] In some exemplary embodiments of the present invention, a population of nanocomposite particles is provided that includes (a) graphene nanoparticles and (b) poly(ethyleneimine) (PEI) grafted thereto.

[0027] In some exemplary embodiments of the present invention, a population of nanocomposite particles is provided that includes (a) carbon black nanoparticles and (b) poly(ethyleneimine) (PEI) grafted thereto.

[0028] For each population of nanocomposite particles defined above:

[0029] In some embodiments, the population of nanocomposite particles described above does not have an intervening layer between the nanoparticles and the PEI. Alternatively or additionally, in some embodiments, the population of nanocomposite particles described above has nanoparticles with an average size between 5 and 100 nm. Alternatively or additionally, in some embodiments, the population of nanocomposite particles described above has a molecular weight of PEI of at least 600 g / mole. Alternatively or additionally, in some embodiments, the population of nanocomposite particles described above has a molecular weight of PEI of 100,000 g / mole or less.

[0030] In some exemplary embodiments of the present invention, an organic solvent (e.g., ethanol) is provided, which includes the steps of (a) adding at least 5% poly(ethyleneimine) (PEI) on a w / w basis to nanoparticles dispersed in ethanol, (b) adding at least 0.1% benzoyl peroxide (BP) on a w / w basis to the nanoparticles, and (c) sonicating. In some embodiments, the method includes sonicating the nanoparticles in the organic solvent (e.g., ethanol). Alternatively or additionally, in some embodiments, the nanoparticles include fumed silica and / or methacrylic silica and / or aluminum oxide (Al2O3) and / or ZnO and / or zeolite and / or TiO2 and / or carbon nanotubes and / or graphene and / or carbon black. Alternatively or additionally, in some embodiments, the method includes adding at least 30% PEI to the nanoparticles. Alternatively or additionally, in some embodiments, the method includes adding at least 100% PEI to the nanoparticles. Alternatively or additionally, in some embodiments, the method includes adding at least 1% BP to the nanoparticles. Alternatively or additionally, in some embodiments, the method includes adding at least 2% BP to the nanoparticles. Alternatively or additionally, in some embodiments, the method includes washing the nanoparticles with ethanol and / or another organic solvent. Alternatively or additionally, in some embodiments, the method includes extracting the ungrafted PEI with xylene. Alternatively or additionally, in some embodiments, the method includes cooling the ethanol (or other solvent) to 4° C. during sonication. Alternatively or additionally, in some embodiments, the method includes incubating at room temperature overnight.

[0031] In some exemplary embodiments of the present invention, a method is provided that includes the steps of: (a) premixing PEI coated nanoparticles with a polymeric material to form a premix; (b) mixing the premix with additional polymeric material to form a final mixture; and (c) extruding the final mixture. In some embodiments, the polymeric material and / or the additional polymeric material are recycled. Alternatively or additionally, in some embodiments, the method includes adding a filler during mixing. Alternatively or additionally, in some embodiments, the method includes adding a filler during extrusion. Alternatively or additionally, in some embodiments, the polymeric material and the additional polymeric material each independently comprise at least one material selected from the group consisting of polyvinyl chloride (PVC), polyethylene (PE, LDPE, HDPE, PEX), polypropylene (PP), polycarbonate (PC), polyamide (PA), polyacrylate, polymethacrylate (PAM), polystyrene (PS), ethylene vinyl alcohol (EVOH), ethylene vinyl acetate (EVA), isoprene, styrene-isoprene-styrene (SIS) block copolymer, butadiene, acrylonitrile butadiene styrene (ABS). Alternatively or additionally, in some embodiments, the final mixture comprises at least 0.01% (W / W) nanoparticles coated with PEI. Alternatively or additionally, according to various exemplary embodiments of the present invention, the final mixture comprises no more than 25% (W / W) nanoparticles coated with PEI. Further embodiments of the present invention relate to products produced by the above methods.

[0032] In some exemplary embodiments of the present invention, a method is provided that includes the steps of (a) dispersing PEI-coated nanoparticles in a liquid medium to form a suspension, (b) applying the suspension to a surface of an article, and (c) evaporating the liquid medium. In some embodiments, the method includes gelling the liquid medium. Alternatively or additionally, in some embodiments, the liquid medium includes water. Alternatively or additionally, in some embodiments, the liquid medium includes an organic solvent. Alternatively or additionally, in some embodiments, the organic solvent includes ethanol. Alternatively or additionally, in some embodiments, the PEI-coated nanoparticles include at least one member selected from the group consisting of silica nanoparticles, methacrylic silica nanoparticles, aluminum oxide (Al2O3) nanoparticles, ZnO nanoparticles, zeolite nanoparticles, TiO2 nanoparticles, carbon nanotube nanoparticles, and graphene nanoparticles. Alternatively or additionally, in some embodiments, the PEI-coated nanoparticles are present in the liquid medium at a concentration of at least 0.01% W / V. Alternatively or additionally, in some embodiments, the applying step comprises at least one action selected from the group consisting of spraying, brushing, doping, rolling, smear coating, and dipping.Alternatively or additionally, in some embodiments, the product comprises at least one material selected from the group consisting of polyvinyl chloride (PVC), polyethylene (PE, LDPE, HDPE, PEX), polypropylene (PP), polycarbonate (PC), polyamide (PA), polyacrylate, polymethacrylate (PAM), polystyrene (PS), high density polystyrene (HIPS), ethylene vinyl alcohol (EVOH), ethylene vinyl acetate (EVA), isoprene, styrene-isoprene-styrene (SIS) block copolymer, butadiene, acrylonitrile butadiene styrene (ABS).

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention belongs. Suitable methods and materials are described below, but methods and materials similar or equivalent to those described herein can be used to practice the present invention. In case of conflict, the patent specification, including definitions, will control. All materials, methods, and examples are illustrative only and are not intended to be limiting.

[0034] The terms "comprising" and "including," or grammatical variations thereof, as used herein, should be construed as specifying the inclusion of the recited features, integers, actions, or components without precluding the addition of one or more additional features, integers, actions, components, or groups thereof. This term is broader than and includes the terms "consisting of" and "consisting essentially of" as defined in the U.S. Patent and Trademark Office Manual of Patent Examining Procedures. Thus, any statement that an embodiment "comprises" or "comprises" a feature is a specific statement that a subembodiment "consists essentially of" and / or "consists of" the recited feature.

[0035] The phrase "consisting essentially of" or grammatical variations thereof, as used herein, should be construed as specifying the recited features, integers, steps, or components, but does not preclude the addition of one or more additional features, integers, steps, components, or groups thereof, so long as such additional features, integers, steps, components, or groups thereof do not materially alter the basic and novel characteristics of the composition, apparatus, or method recited in the claims.

[0036] The term "compatible with" as used in this specification and the appended claims imposes additional structural constraints on the aforementioned components.

[0037] The term "method" refers to methods, means, techniques, and procedures for accomplishing a given task, including, but not limited to, methods, means, techniques, and procedures that are known or that are known and readily developed by those skilled in the art of architecture and / or computer science.

[0038] Percentages (%) are W / W (weight / weight) unless otherwise stated.

[0039] The molecular weights shown are based on the manufacturer's product data sheets but may vary depending on the actual measurement conditions. [Brief description of the drawings]

[0040] In order to understand the invention and to see how it may be carried out in practice, embodiments will now be described, by way of non-limiting example only, with reference to the accompanying figures, in which identical and similar structures, elements or portions thereof that appear in more than one figure are generally labeled with the same or similar reference symbols in the figures in which they appear. Dimensions of components and features shown in the figures have been chosen primarily for convenience and clarity of presentation and are not necessarily to scale. The accompanying figures are as follows:

[0041] [Figure 1] 1 is a schematic overview of a process for forming nanocomposite particles according to some exemplary embodiments of the present invention. [Diagram 2] FIG. 1 is a simplified flow diagram of a method for producing nanocomposite particles, according to some exemplary embodiments of the present invention. [Diagram 3] FIG. 1 is a simplified flow diagram of a method for incorporating nanocomposite particles into a polymeric material, according to some exemplary embodiments of the present invention. [Figure 4] 1 is a simplified flow diagram of a method for applying nanocomposite particles to a surface of an article, according to some exemplary embodiments of the present invention. [Diagram 5]FIG. 1 shows a plot of FTIR spectra (absorbance as a function of wavenumber / cm) of pristine silica Aerosil 200 (dash-dotted line), neat PEI 25K (dotted line), neat PEI 10K (solid line), SC25-04 (dash-dotted line), and SC10-04 (dashed line) before extraction with 3:1 PEI and 2.0% BP. [Figure 6A] 1 is a plot of FTIR spectra (absorbance as a function of wavenumber / cm) of nanocomposite particles according to an exemplary embodiment of the present invention before (top line) and after (bottom line) extraction with xylene. [Figure 6B] 1 is a plot of FTIR spectra (absorbance as a function of wavenumber / cm) of nanocomposite particles according to an exemplary embodiment of the present invention before (top line) and after (bottom line) extraction with xylene. [Figure 7A] FIG. 13 is a TGA thermogram (wt%) as a function of temperature (° C.) of a nanocomposite particle (SC800-04) according to an exemplary embodiment of the present invention before (solid line) and after (dotted line) xylene extraction, with neat PEI (dashed line) for reference. [Figure 7B] For reference, DTG thermograms [Weight derivative (% / °C)] as a function of temperature (°C) of nanocomposite particles according to an exemplary embodiment of the present invention (SC800-04) before (solid line) and after (dotted line) xylene extraction with neat PEI (dashed line). [Figure 7C] 1 is a TGA thermogram (wt %) as a function of temperature (° C.) of a nanocomposite particle according to an exemplary embodiment of the present invention before (blue line) and after (orange line) xylene extraction. [Figure 7D] 1 is a DTG thermogram [weight derivative (% / ° C.)] as a function of temperature (° C.) of a nanocomposite particle according to an exemplary embodiment of the present invention before (blue line) and after (orange line) xylene extraction. [Figure 8]13A-C are TGA thermograms (wt %) of nanocomposite particles according to exemplary embodiments of the present invention after xylene extraction at weight ratios of 1:3 (dashed line, SC25-Y), 3:1 (dotted line), and 1:1 (solid line) for a BP concentration of 0.5% and PEI MW 25,000. [Figure 9A] 1 shows TGA thermograms (wt % as a function of temperature (° C.)) of nanocomposite particles (SC25-Y) according to an exemplary embodiment of the present invention after xylene extraction at weight ratios of 3:1 (dotted line), 1:1 (solid line), and 1:3 (dashed line) for a BP concentration of 1.0% and PEI MW 25,000. [Figure 9B] 13 is a TGA thermogram (wt % as a function of temperature) of nanocomposite particles SC25-Y according to an exemplary embodiment of the present invention after xylene extraction at weight ratios of 3:1 (dotted line), 1:1 (solid line), and 1:3 (dashed line) for a BP concentration of 2.0% and PEI MW 25,000. [Figure 9C] FIG. 9 is a 3D bar graph of the grafted PEI fraction of the TGA thermograms of FIG. 8, FIG. 9A and FIG. 9B. [Figure 10] 1 shows TGA thermograms (wt %) of nanocomposite particles according to an exemplary embodiment of the present invention after xylene extraction with BP concentrations of 2.0% (top line), 1.0% (middle line) and 0.5% (bottom line) with PEI of 600 MW and 1:3 weight ratio. [Figure 11A] 1 shows TGA thermograms (wt %) of nanocomposite particles according to an exemplary embodiment of the present invention after xylene extraction with BP concentrations of 2.0% (lower line), 1.0% (upper line), and 0.5% (middle line) with PEI MW 10,000 and weight ratio of 3:1. [Figure 11B] 13 is a TGA thermogram of nanocomposite particles according to an exemplary embodiment of the present invention (wt %) as a function of temperature (° C.) after xylene extraction with PEI MW 25000 and weight ratio of 3:1 with BP concentrations of 2.0% (blue line), 1.0% (orange line) and 0.5% (green line). [Figure 12]1 shows TGA thermograms (wt %) of nanocomposite particles according to an exemplary embodiment of the present invention after xylene extraction with BP concentrations of 2.0% (middle line), 1.0% (top line) and 0.5% (bottom line) at a 1:1 weight ratio. [Figure 13A] 1 is a TGA thermogram (weight % as a function of temperature (° C.)) of nanocomposite particles SC600-6 and SC800-06 according to an exemplary embodiment of the present invention after xylene extraction for PEI 600MW (top line), PEI 800MW (bottom line). [Figure 13B] 4 is a TGA thermogram (wt % as a function of temperature (° C.)) of nanocomposite particles according to an exemplary embodiment of the present invention, b) SC600-09 and SC25-09 after xylene extraction for PEI 600 MW (top line), and PEI 25,000 MW (blue line). [Figure 13C] 1 is a TGA thermogram (weight % as a function of temperature (° C.)) of nanocomposite particles SC800-08 and SC25-08 according to an exemplary embodiment of the present invention after xylene extraction for PEI 600 MW (top line), and PEI 25,000 MW (bottom line). [Figure 13D] 1 is a TGA thermogram (weight % as a function of temperature (° C.)) of nanocomposite particles SC10-05 and SC25-05 according to an exemplary embodiment of the present invention after xylene extraction for PEI 10,000 MW (top line), and PEI 25,000 MW (bottom line). [Figure 14A] 1 shows TGA thermograms (wt % as a function of temperature (° C.)) of nanocomposite particles according to an exemplary embodiment of the present invention after xylene extraction at a weight ratio of 3:1 and a BP concentration of 0.5% for AEROSIL 200 (third line from the top), AEROSIL R972 (top line), AEROSIL R711 (bottom line), and Aeroxide Alu C (second line). [Figure 14B]1 shows DTG thermograms (derived weight (% / °C) as a function of temperature (°C)) of nanocomposite particles according to an exemplary embodiment of the present invention after xylene extraction at a weight ratio of 3:1 and a BP concentration of 0.5% for AEROSIL 200 (yellow line), AEROSIL R972 (grey line), AEROSIL R711 (orange line), and Aeroxide Alu C (blue line). [Figure 15A] FTIR spectra (absorbance as a function of wavenumber / cm) of nanocomposite particles according to exemplary embodiments of the invention after xylene extraction at a weight ratio of 3:1 and a BP concentration of 0.5% for AEROSIL 200 (yellow line), AEROSIL R972 (grey line), AEROSIL R711 (orange line), and Aeroxide Alu C (blue line). [Figure 15B] 1 is a bar graph showing the % weight loss of PEI nanocomposite particles according to various exemplary embodiments of the present invention based on different particle types (AEROSIL 200, AEROSIL R972, AEROSIL R711, and Aeroxide Alu C). [Figure 16A] FIG. 2 is a high-resolution scanning electron micrograph (HRSEM) of ungrafted silica nanoparticles (magnification 50,000). [Figure 16B] High-resolution scanning electron micrograph (HRSEM) of PEI 25,000 MW (magnification 5,000). [Figure 16C] A mixture of silica nanoparticles and PEI 25,000 MW (magnification 50,000). [Figure 16D] 1 shows nanocomposite particles according to an exemplary embodiment of the present invention (sample SC25-07 before xylene extraction) (magnification 50,000). [Figure 17A] 1 is an HRSEM photograph (100,000 magnification) of nanocomposite particles (sample SC25-07 before xylene extraction) according to an exemplary embodiment of the present invention. [Figure 17B] 1 is an HRSEM photograph (100,000 magnification) of nanocomposite particles (sample SC25-07 before xylene extraction) according to an exemplary embodiment of the present invention. [Figure 18] FIG. 1 is a bar graph showing total emissions in PPM measured by GCMS after 30 minutes at 90° C. and 60 minutes at 120° C. for recycled PVC with blowing agent, where R represents an untreated reference sample, C represents a sample with 0.5% of a commercial odor-reducing additive, and E represents a sample with 0.5% PEI nanocomposite particles according to an exemplary embodiment of the present invention. [Figure 19] 1 is a bar graph showing the odor perceived in arbitrary units by a panel of five human testers for a Plastofil G1 panel (reference), the same panel with 2.0% of a commercial odor-reducing additive (benchmark), the same panel with non-grafted PEI (0.25% neat PEI), and the same panel with PEI nanocomposite particles according to an exemplary embodiment of the present invention (0.25% SC-07 25). [Figure 20] 1 is a bar graph showing % weight loss as a function of PB concentration (%) of PEI 25,000 MW nanocomposite particles having different SI:PEI weight ratios according to various exemplary embodiments of the present invention. [Figure 21] 1 is a bar graph showing % weight loss as a function of PB concentration (%) of PEI 10,000 MW nanocomposite particles having different SI:PEI weight ratios according to various exemplary embodiments of the present invention. [Figure 22] 1 is a bar graph showing % weight loss as a function of PB concentration (%) of PEI 800 MW nanocomposite particles having different SI:PEI weight ratios according to various exemplary embodiments of the present invention. [Figure 23A] FIG. 2 is a TGA thermogram (wt %) as a function of temperature (° C.) of a nanocomposite particle according to an exemplary embodiment of the present invention, in which EC300 carbon black nanoparticles are grafted to PEI 25,000 MW after xylene extraction. [Figure 23B] FIG. 23B is a TGA thermogram (wt %) as a function of temperature (° C.) of PEI 25,000 MW as the reference standard for FIG. [Figure 23C]FIG. 23D is a DTG thermogram (weight derivative (% / ° C.) as a function of temperature (° C.)) of a nanocomposite particle according to an exemplary embodiment of the invention, in which EC300 carbon black nanoparticles are grafted to PEI 25,000 MW after xylene extraction (similar to FIG. 23A). [Figure 23D] DTG thermogram ([weight derivative (% / °C)] as a function of temperature (°C)) of PEI 25,000 MW as a reference standard for Figure 23C. [Figure 24A] FIG. 2 is a TGA thermogram (wt %) as a function of temperature (° C.) of a nanocomposite particle according to an exemplary embodiment of the present invention, in which SW07 single-walled carbon nanotube nanoparticles are grafted to PEI 25,000 MW after xylene extraction. [Figure 24B] FIG. 24B is a TGA thermogram (wt %) as a function of temperature (° C.) of SW07 carbon nanotube nanoparticles without PEI as a reference standard. [Figure 24C] FIG. 2 is a DTG thermogram (weight derivative (% / °C) as a function of temperature (°C)) of a nanocomposite particle according to an exemplary embodiment of the present invention, in which SW07 single-walled carbon nanotube nanoparticles are grafted to PEI 25,000 MW after xylene extraction. [Figure 24D] FIG. 24C is a DTG thermogram ([weight derivative (% / ° C.)] as a function of temperature (° C.)) of SW07 carbon nanotube nanoparticles without PEI as a reference standard. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0042] SUMMARY OF THE DISCLOSURE Embodiments of the present invention relate to nanocomposite particles and methods of making and using them.

[0043] Specifically, some embodiments of the present invention can be used to graft PEI directly onto nanoparticles without an intervening layer. Alternatively or additionally, in some embodiments, nanoparticles coated with PEI (whether by direct grafting or otherwise) exhibit greater odor reducing capabilities than PEI alone or nanoparticles alone.

[0044] The principles and operation of coated nanoparticles and / or ds according to exemplary embodiments of the present invention may be better understood with reference to the drawings and accompanying description.

[0045] Before describing at least one embodiment of the invention in detail, it is to be understood that the invention is not limited in its application to the details set forth in the following description or illustrated by the examples. The invention is capable of other embodiments or of being practiced or carried out in various ways. Also, it is to be understood that the phraseology and terminology used herein is for the purpose of description and should not be regarded as limiting.

[0046] Exemplary Nanocomposite Particles Some exemplary embodiments of the present invention relate to a population of nanocomposite particles comprising hydrophilic fumed silica nanoparticles and poly(ethyleneimine) (PEI) grafted thereto. According to these embodiments, there is no intervening layer between the nanoparticles and the PEI. Exemplary nanoparticles suitable for use in these embodiments include AEROSIL™ 200 and AEROSIL 300 and AEROSIL 300 / 30 (EVONIK, Germany).

[0047] Some exemplary embodiments of the present invention relate to a population of nanocomposite particles comprising hydrophobic fumed silica nanoparticles and poly(ethyleneimine) (PEI) grafted thereto. Exemplary nanoparticles suitable for use in these embodiments include AEROSIL R972 (hydrophobic, size 16 nm, EVONIK, Germany).

[0048] Some exemplary embodiments of the present invention relate to a population of nanocomposite particles comprising methacrylic silica nanoparticles and poly(ethyleneimine) (PEI) grafted thereto. Exemplary nanoparticles suitable for use in these embodiments include AEROSIL R711 (size 12 nm, EVONIK, Germany).

[0049] Some exemplary embodiments of the present invention relate to a population of nanocomposite particles comprising aluminum oxide (Al2O3) nanoparticles and poly(ethyleneimine) (PEI) grafted thereto. Exemplary nanoparticles suitable for use in these embodiments include Aeroxide Alu C (Al2O3, EVONIK, Germany).

[0050] Some exemplary embodiments of the present invention relate to a population of nanocomposite particles comprising zinc oxide (ZnO) nanoparticles and poly(ethyleneimine) (PEI) grafted thereto. Exemplary nanoparticles suitable for use in these embodiments include AEROSIL R972 (hydrophobic, size 16 nm, EVONIK, Germany).

[0051] Some exemplary embodiments of the present invention relate to a population of nanocomposite particles comprising zeolite nanoparticles and poly(ethyleneimine) (PEI) grafted thereto. Exemplary nanoparticles suitable for use in these embodiments include Zeoflair 100, Zeoflair 110, Zeoflair 800 (ZEOCHEM, USA), and ZSM 5 (Zeolyst, USA).

[0052] Some exemplary embodiments of the present invention relate to a population of nanocomposite particles comprising titanium dioxide (TiO2) nanoparticles and poly(ethyleneimine) (PEI) grafted thereto. Exemplary nanoparticles suitable for use in these embodiments include Aeroxide P25 (EVONIK, Germany).

[0053] Some exemplary embodiments of the present invention relate to a population of carbon nanotube nanoparticles or nanocomposite particles comprising carbon black and poly(ethyleneimine) (PEI) grafted thereto. Exemplary carbon nanotube nanoparticles suitable for use in these embodiments include NC7000 (Nanocyl SA, Belgium) and Tuball SWNT (OCSIAL, Luxembourg).

[0054] Exemplary carbon nanotube nanoparticles suitable for use in these embodiments include Ketjenblack EC-300 and EC-600 (Nouryon, The Netherlands).

[0055] Some exemplary embodiments of the present invention relate to a population of nanocomposite particles comprising graphene nanoparticles and poly(ethyleneimine) (PEI) grafted thereto. Exemplary nanoparticles suitable for use in these embodiments include reduced graphene oxide or graphene 300 (Sigma Aldrich, St. Louis, MO, USA).

[0056] In some exemplary embodiments of the various nanocomposite particles described above, there is no intervening layer between the nanoparticles and the PEI. In some exemplary embodiments of the various nanocomposite particles described above, the nanoparticles have an average size of 5-100 nm before PEI grafting. According to various exemplary embodiments of the present invention, the PEI increases the nanoparticle size from 1 nm up to 15 nm.

[0057] In some exemplary embodiments of the various nanocomposite particles described above, the molecular weight of the PEI is at least 600 g / mol. Alternatively or additionally, in some embodiments, the molecular weight of the PEI does not exceed 100,000 g / mol.

[0058] (Exemplary Manufacturing Method) FIG. 2 is a simplified flow diagram of a method, generally designated 200, for producing nanocomposite particles, according to some exemplary embodiments of the present invention.

[0059] The depicted exemplary method 200 includes steps 210 of adding at least 5% poly(ethyleneimine) (PEI) on a w / w basis to nanoparticles dispersed in ethanol, 220 of adding at least 0.1% benzoyl peroxide (BP) on a w / w basis to the nanoparticles, and 230 of sonicating. In some exemplary embodiments of the invention, sonication 230 contributes to grafting of PEI to the particles. Alternatively or additionally, in some embodiments, BP provides free radicals that contribute to initiating the grafting reaction. According to further exemplary embodiments of the invention, the nanoparticles are dispersed in other organic solvents instead of ethanol. According to various exemplary embodiments of the invention, suitable solvents include, but are not limited to, toluene, xylene, methanol, isopropyl alcohol, and propanol.

[0060] In some exemplary embodiments of the invention, initial dispersion 210 is achieved by sonicating 208 the nanoparticles in an organic solvent (e.g., ethanol). In some embodiments, sonication contributes to the dispersion.

[0061] In some exemplary embodiments of the invention, the nanoparticles comprise fumed silica (hydrophobic and / or hydrophilic). Alternatively or additionally, in some embodiments, the nanoparticles comprise methacrylic silica. Alternatively or additionally, in some embodiments, the nanoparticles comprise aluminum oxide (Al2O3). Alternatively or additionally, in some embodiments, the nanoparticles comprise ZnO (hydrophobic and / or hydrophilic). Alternatively or additionally, in some embodiments, the nanoparticles comprise zeolite. Alternatively or additionally, in some embodiments, the nanoparticles comprise TiO2. Alternatively or additionally, in some embodiments, the nanoparticles comprise carbon nanotubes. Alternatively or additionally, in some embodiments, the nanoparticles comprise graphene. Alternatively or additionally, in some embodiments, the nanoparticles comprise carbon black.

[0062] In some exemplary embodiments of the invention, the method includes adding at least 30% or at least 100% PEI to the nanoparticles. According to various exemplary embodiments of the invention, the amount of PEI added ranges from 0.1% to 500% as described above.

[0063] In some exemplary embodiments of the invention, the method includes adding at least 1% BP or at least 3% BP to the nanoparticles. According to various exemplary embodiments of the invention, the amount of BP added ranges from 0.1% to 3% as described above. In the depicted embodiment, the method 200 includes washing 240 the nanoparticles with ethanol. According to various exemplary embodiments of the invention, the ethanol washing 240 is accomplished by vacuum filtration and / or centrifugation and / or evaporation. The ethanol washing 240 contributes to the reduction of BP and / or unbound PEI. Alternatively or additionally, in some embodiments, the method 200 includes extracting 250 the ungrafted PEI with xylene. According to various exemplary embodiments of the invention, the xylene extraction 250 is performed for 2 to 12 hours, 4 to 10 hours, 5 to 8 hours, or 6.5 to 7.5 hours. In some embodiments, hot xylene is used. Alternatively or additionally, in some embodiments, method 200 includes cooling the ethanol to 4° C. during sonication 230 and / or 208. Alternatively or additionally, in some embodiments, method 200 includes incubating overnight at room temperature after sonication 230. In some embodiments, this incubation contributes to an increase in the amount of PEI that is grafted.

[0064] (Example Usage) FIG. 3 is a simplified flow diagram of a method, generally designated 300, for incorporating nanocomposite particles into a polymeric material, according to some exemplary embodiments of the present invention.

[0065] The depicted exemplary method 300 includes premixing 310 the PEI coated nanoparticles with a polymeric material to form a premix, and mixing 320 additional polymeric material with the premix to form a final mixture. In the depicted embodiment, the method 300 includes extruding 330 the final mixture. In some exemplary embodiments of the invention, the mixing 320 and / or the premix 310 comprises a dry blend. According to various exemplary embodiments of the invention, the extrusion 330 is extrusion to a desired concentration or extrusion with concentration followed by dilution.

[0066] In some embodiments of method 300, the polymeric material and / or the additional polymeric material are recycled. Alternatively or additionally, in some embodiments, the PEI coated nanoparticles are as described above and / or obtained from method 200 described above.

[0067] In the illustrated embodiment, the method 300 includes a step 340 of adding a filler during mixing 320. Alternatively or additionally, in some embodiments, the method 300 includes a step 350 of adding a filler during extrusion 330. In some embodiments, the filler includes a non-polymeric material (e.g., ceramic or mineral).

[0068] In some exemplary embodiments of the invention, the polymeric material in 310 and the additional polymeric material 320 each independently comprise at least one material selected from the group consisting of polyvinyl chloride (PVC), polyethylene (PE, LDPE, HDPE, PEX), polypropylene (PP), polycarbonate (PC), polyamide (PA), polyacrylate, polymethacrylate (PAM), polystyrene (PS), high density polystyrene (HIPS), ethylene vinyl alcohol (EVOH), ethylene vinyl acetate (EVA), isoprene, styrene-isoprene-styrene (SIS) block copolymer, butadiene, acrylonitrile butadiene styrene (ABS).

[0069] In some exemplary embodiments of the invention, the final mixture produced in 310 comprises at least 0.01% (w / w) PEI coated nanoparticles. Alternatively or additionally, in some embodiments, the final mixture produced in 310 comprises no more than 25% (w / w) PEI coated nanoparticles. According to various exemplary embodiments of the invention, the final mixture produced in 310 comprises at least 0.05%, at least 0.1%, at least 0.25%, at least 0.5%, at least 0.75%, at least 1%, at least 2%, at least 4%, at least 6%, at least 8%, at least 10%, or any intermediate or higher percentage. Alternatively or additionally, according to various exemplary embodiments of the present invention, the final mixture produced in 310 includes less than 10%, less than 8%, less than 10%, less than 8%, less than 6%, less than 4%, less than 2%, less than 1%, less than 0.75%, less than 0.5%, less than 0.4%, less than 0.3%, less than 0.2%, less than 0.1%, or intermediate or lower percentages.

[0070] According to various exemplary embodiments of the present invention, the extruded final mixture produced at 330 is used in one or more industrial processes including, but not limited to, injection molding, blow molding, woven mats, rotational molding, additive manufacturing, and vacuum forming.

[0071] Other exemplary embodiments of the present invention relate to any product produced by method 300 or variations thereof.

[0072] Further Exemplary Uses FIG. 4 is a simplified flow diagram of a method, generally designated 400, for applying nanocomposite particles to a surface of an article, according to some exemplary embodiments of the present invention.

[0073] The depicted exemplary method 400 includes dispersing PEI-coated nanoparticles in a liquid medium to form a suspension 410. In some embodiments, the PEI-coated nanoparticles are as described above and / or result from method 200 described above.

[0074] In the depicted embodiment, the method 400 includes applying 420 the suspension to a surface of the product and evaporating 430 the liquid medium. Alternatively or additionally, in some embodiments, the method 400 includes gelling 440 the liquid medium. In some exemplary embodiments of the invention, the gelling includes crosslinking of polymers and / or hydrogels. In some exemplary embodiments of the invention, the liquid medium includes water. Alternatively or additionally, in some embodiments, the liquid medium includes an organic solvent. In some exemplary embodiments of the invention, the organic solvent includes ethanol.

[0075] According to various exemplary embodiments of the present invention, the PEI-coated nanoparticles include at least one member selected from the group consisting of silica nanoparticles, methacrylic silica nanoparticles, aluminum oxide (Al2O3) nanoparticles, ZnO nanoparticles, zeolite nanoparticles, TiO2, carbon nanotube nanoparticles, and graphene nanoparticles. According to various exemplary embodiments of the present invention, the nanoparticles are hydrophilic and / or hydrophobic nanoparticles.

[0076] In some embodiments of method 400, the PEI coated nanoparticles are present in the liquid medium at a concentration of at least 0.01% W / W. According to various exemplary embodiments of the invention, the PEI coated nanoparticles are present in the liquid medium at a concentration of at least 0.05%, at least 0.1%, at least 0.25%, at least 0.5%, at least 0.75%, at least 1%, at least 2%, at least 4%, at least 6%, at least 8%, at least 10%, or intermediate or higher percentages. Alternatively or additionally, according to various exemplary embodiments of the invention, the PEI coated nanoparticles are present in the liquid medium at less than 10%, less than 8%, less than 6%, less than 4%, less than 2%, less than 1%, less than 0.75%, less than 0.5%, less than 0.4%, less than 0.3%, less than 0.2%, less than 0.1%, or intermediate or lower percentages.

[0077] Alternatively or additionally, in some embodiments of the method 400, the applying step includes at least one action selected from the group consisting of spraying, brushing, doping, rolling, smear coating, and dipping.

[0078] According to various exemplary embodiments of the present invention, the product at 420 comprises at least one material selected from the group consisting of polyvinyl chloride (PVC), polyethylene (PE, LDPE, HDPE, PEX), polypropylene (PP), polycarbonate (PC), polyamide (PA), polyacrylate, polymethacrylate (PAM), polystyrene (PS), ethylene vinyl acetate (EVA), isoprene, styrene-isoprene-styrene (SIS) block copolymer, butadiene, acrylonitrile butadiene styrene (ABS).

[0079] It is expected that many new polymeric materials and / or types of nanoparticles will be developed during the life of this patent, and the scope of the present invention a priori includes all such new technologies.

[0080] As used herein, the term "about" refers to ±10%.

[0081] While the present invention has been described in conjunction with specific embodiments thereof, it is evident that many alternatives, modifications, and variations will be apparent to those skilled in the art. Accordingly, it is intended to embrace all such alternatives, modifications, and variations that fall within the spirit and broad scope of the appended claims.

[0082] In particular, various numerical indicators are utilized. It should be understood that these numerical indicators may further vary based on various technical principles, materials, intended uses and designs incorporated in various embodiments of the present invention. Furthermore, components and / or operations that belong to the exemplary embodiments of the present invention and are shown as single units may be divided into sub-units. Conversely, components and / or operations that belong to the exemplary embodiments of the present invention and are shown as sub-units / individual operations may be combined into a single unit / operation with the functionality described / illustrated.

[0083] Alternatively or additionally, features used to describe a method may be used to characterize an apparatus and features used to describe an apparatus may be used to characterize a method.

[0084] It is further understood that the individual features described above can be combined in all possible combinations and subcombinations to generate further embodiments of the present invention. The foregoing examples are exemplary in nature and are not intended to limit the scope of the invention, which is defined solely by the claims that follow.

[0085] Each description of an embodiment of the invention that includes a particular feature, part, component, module, or process is an explicit description that there are additional embodiments of the invention that do not include the described feature, part, component, module, or process.

[0086] Alternatively or additionally, various exemplary embodiments of the present invention exclude any particular feature, part, component, module, process or element not specifically disclosed herein.

[0087] In particular, although the present invention has been described in the context of particular types of nanoparticles and particular industrial processes, it may be used with other nanoparticle types and / or in the context of other industrial processes.

[0088] All publications, references, patents, and patent applications mentioned in this specification are herein incorporated by reference in their entirety to the same extent as if each individual publication, patent, or patent application was specifically and individually indicated to be incorporated by reference herein. Further, citation or identification of any reference in this application shall not be construed as an admission that such reference is available as prior art to the present invention.

[0089] The terms "including" and "having," along with their conjugations, as used herein mean "including, but not necessarily limited to."

[0090] Additional objects, advantages, and novel features of various embodiments of the present invention will become apparent to those skilled in the art upon examination of the following examples, which are not intended to be limiting. Additionally, each of the various embodiments and aspects of the present invention as delineated above and as claimed in the claims section below finds experimental support in the following examples. EXAMPLES

[0091] Reference is now made to the following examples, which together with the above descriptions illustrate the invention in a non-limiting fashion.

[0092] The following materials and methods are used in carrying out the experiments described in the examples below.

[0093] (material) PEI: Commercially available polyethyleneimine polymers 600 (Alfa Acer, Japan), 800 (D-BASF, Germany), 10K (Alfa Acer, USA) and 25K (D-BASF, Germany) were used as received without further purification. BP: Recrystallized benzoyl peroxide was used as the initiator (Alfa Acer, UK). Silica nanoparticles: AEROSIL 200 (hydrophilic, 12 nm), AEROSIL R972 (hydrophobic, size 16 nm), AEROSIL R711 (methacrylic silica, size 12 nm), all from EVONIK (Germany). Ethanol: 99.9% (Romical, Israel) was used as the solvent. Xylene:Xylene (Carlo Erba Reagents, France) was used to extract the ungrafted PEI fraction.

[0094] (method) TGA: The thermal stability of the PEI / Si nanocomposites was determined by thermogravimetric analysis (TGA) using a TA Instruments Q5000 thermogravimetric analyzer (TA Instruments, USA). The temperature range was 25-600 °C with a heating rate of 10 °C / min, and the weight loss was monitored as a function of temperature. The analysis was performed under nitrogen atmosphere at a flow rate of 25 mL / min. FTIR: Fourier transform infrared (FTIR) spectra of the samples were obtained in the range of 650–4000 cm-1 to obtain information about the chemical composition of the SiO2 nanoparticles grafted on their surface by the polymer PEI using a Thermo 6700 FTIR instrument equipped with a Smart iTR diamond ATR device. HRSEM: The morphology of the silica PEI-grafted nanoparticles before extraction was studied by high-resolution scanning electron microscopy (HRSEM). Samples were sputtered with carbon before observation and examined with an HRSEM (Carl Zeiss Ultra Plus) at an accelerating voltage of 1 keV.

[0095] Example 1: Preparation of nanocomposites PEI / Si nanocomposites were synthesized as shown in the schematic diagram in FIG. 1. In (1), a measured amount of nanoparticles (e.g., fumed silica or alumina) was added to 20 mL of ethanol. The mixture was sonicated (5 min in lab scale) to disperse the nanoparticles. In (2), poly(ethyleneimine) (PEI) with different molecular weights (600, 800, 10,000 and 25,000 g / mol) in different weight ratios of NP:PEI (3:1, 1:1 and 1:3) and different concentrations (0.5%, 1% and 2%) of benzoyl peroxide initiator were added to the dispersion, followed by sonication at 4° C. as listed in Table 1.

[0096] Table 1. Preparation of nanocomposite materials based on Aerosil 200 and benzoyl peroxide (BP), *XX refers to PEI MW (600 for 10,000, 800, 10, and 25 for 25,000 g / mol). [Table 1]

[0097] The system was left at room temperature overnight without stirring to complete the reaction. The resulting gel-like nanocomposite was filtered and washed several times with excess ethanol using a Millipore vacuum filter device equipped with a 70 nm pore size membrane. The filter cake solid was then dried overnight in a vacuum oven to obtain a fine white powder.

[0098] Two types of PEI fractions are present in the final solid, as shown in Figure 1(2): unattached (not grafted to nanoparticles) PEI and grafted PEI.

[0099] To further study the grafting efficiency, an extraction procedure was performed. An aliquot of the filter cake solid was immersed in hot xylene for 7 h. The ungrafted PEI dissolved in the xylene, leaving the PEI-grafted nanoparticles at the bottom of the reactor. The grafted nanoparticles were then characterized using thermogravimetric analysis (TGA) and Fourier transform infrared (FTIR) spectroscopy.

[0100] The effect of different initiator concentrations and weight ratios on the resulting grafted PEI fraction was studied. The nanocomposites showing the highest PEI grafted fraction on the silica surface according to considerable cost-effectiveness were further studied by replacing the hydrophilic silica with hydrophobic silica and other types of nanoparticles such as methacrylic silica and alumina.

[0101] Example 2: FTIR of AEROSIL 200 based nanocomposites To study the effect of PEI MW on FTIR measurements, unextracted samples were used. Figure 5 shows the FTIR spectra of Aerosil 200 (dashed line), neat PEI 25K (dotted line), neat PEI 10K (solid line), SC25-04 (dashed line) and SC10-04 (dashed line) before extraction with 3:1 PEI and 2.0% BP.

[0102] Figure 5 shows that all samples have a peak intensity of 1050–780 cm -1 4 shows that the AEROSIL 200 has the same two peaks characteristic of AEROSIL 200 in the range of 0.1 to 1.0 μm.

[0103] The sample with grafted PEI had a peak at 1475 cm -1 and 1561 cm -1 Two additional peaks near and around 3280 cm -1 Absorption bands at 2840 and 2960 cm -1 Two nearby peaks are shown.

[0104] Thus, these additional peaks confirm that PEI was successfully grafted onto the silica surface.

[0105] Example 3: Effect of increasing MW of PEI on FTIR To investigate the effect of increasing the MW of PEI from 10,000 to 25,000, the FTIR spectra of PEI / Si nanocomposites SC10-04 and SC25-04 were compared.

[0106] 6A and 6B show the FTIR spectra of the PEI / Si nanocomposites SC10-04 (FIG. 6a) and SC25-04 (FIG. 6b) before (top line) and after (bottom line) extraction with hot xylene.

[0107] After xylene extraction, 1650 cm -1 A nearby new peak appears in both samples, suggesting that the primary amine is converted to a secondary amine.

[0108] After xylene extraction, 1561 cm -1 The peaks at either completely disappeared or were greatly reduced for PEI 10K and PEI 25K, respectively. The reduction in the amount of organic material is believed to contribute to the reduction in the peak intensity.

[0109] After xylene extraction, N-H2 (approx. 1561 cm -1 ) shows a large decrease in intensity. It is believed that the removed organic compounds had such chemical bonds, i.e., no PEI attached.

[0110] These changes in the spectrum are characteristic of bonds between oxygen atoms from the silanol groups of the silica and nitrogen atoms in the PEI resulting from the grafting of PEI to the nanoparticles. Thus, these changes in the spectrum confirm the grafting of PEI to the particle surface.

[0111] Example 4: Effect of xylene extraction on TGA and DTG The amount of organic compounds (%wt lost is organic, the remainder is inorganic; TGA) and / or the first derivative (1 stTo know the derivative (DTG) peaks related to the thermal stability of the composites, xylene extraction was performed prior to TGA and DTG measurements.

[0112] Usually, when an organic compound is grafted, the thermal stability is altered.

[0113] Figures 7a, 7b, 7c and 7d show the TGA and DTG (first derivative) thermograms of PEI / Si nanocomposites for two different molecular weights of PEI, SC800-04 (Figures 7a and 7b) and SC25-05 (Figures 7c and 7d), before (solid lines) and after (dotted lines) xylene extraction.

[0114] All samples have the same profile regardless of PEI MW, BP concentration or PEI:Si weight ratio.

[0115] Before xylene extraction, the TGA curves (FIGS. 7A and 7C) highlight two weight losses confirmed by the presence of two distinct peaks in the DTG curves (FIGS. 7B and 7D).

[0116] After extraction, only one transition remains, and the temperature of the corresponding peak (289° C. and 316° C. for SC800-04 and SC25-05, respectively) is located near the first peak seen in the unextracted sample.

[0117] These results suggest that the first peak in the unextracted samples (277°C and 314°C for SC800-04 and SC25-05, respectively) is due to the attachment of PEI to the silica surface, while the second peak (352°C or 358°C) reflects the ungrafted PEI fraction.

[0118] It is noted that in all unextracted samples, the decomposition temperature of the attached fraction is around 275° C., except for SC25-05, which is located at a higher temperature.

[0119] For SC800-04, a temperature difference of 12°C (277°C to 289°C) is observed, which may be due to the effect of chain bonding to the silica surface on thermal oxidation resistance, and this temperature change can be seen in each sample.

[0120] These results suggest that the unextracted nanoparticles underwent two decomposition steps of PEI, the first corresponding to the attached PEI chain fraction and the second to the ungrafted PEI fraction, whereas the extracted nanoparticles decomposed in one step with a weight loss corresponding only to the thermal decomposition of the PEI chains grafted onto the silica surface. Furthermore, these results suggest that the transition below 100 °C seen before and after extraction is due to the volatilization of residual ethanol.

[0121] The free PEI fraction is expected to degrade first as a result of its lower molecular weight than that contained in the grafted PEI fraction. One reason that can explain the reversal phenomenon is that the ungrafted PEI is protected by the char barrier effect.

[0122] These results demonstrate that extraction with xylene is efficient in dissolving ungrafted PEI and that PEI is successfully grafted onto the silica surface, resulting in PEI-grafted silica nanoparticles.

[0123] Example 5: Effect of weight ratio on TGA To determine the effect of the SI:PEI weight ratio, different weight ratios were tested while keeping the amount of BP initiator constant.

[0124] FIG. 8 is a TGA thermogram (wt %) as a function of temperature showing the effect of the weight ratio SI:PEI for a 0.5% BP concentration and a PEI MW of 25000.

[0125] The maximum PEI grafted fraction occurred at a weight ratio of 1:1 (solid line, SC25-08), resulting in a weight loss of 29.5%. As the weight ratio decreases (wr3:1, dotted line, SC25-07), i.e., the amount of PEI decreases, a decrease in the grafted fraction is observed (about 21% grafted). This decrease is expected since a lower amount of PEI is used.

[0126] When the weight ratio was increased to 1:3 (dashed line, SC25-09), the amount of grafting was dramatically reduced, with one-third grafted compared to SC25-08 (about 11%). This result suggests that the grafting capacity of the silica surface for PEI was limited at a weight ratio of 1:1. These results also suggest that the high degree of branching of PEI 25K may contribute to steric hindrance when excess PEI is present. These results also suggest that the high degree of branching of PEI 25K may contribute to steric hindrance when excess PEI is present.

[0127] Example 6: Effect of initiator amount on TGA with high MW PEI To determine the effect of initiator amount, two different percentages of BP were tried at two SI:PEI weight ratios using PEI of MW 25000.

[0128] 9A and 9B show TGA thermograms (wt % as a function of temperature) for PEI 25K-based samples at three different weight ratios of 1.0% (FIG. 9a) and 2.0% (FIG. 9b).

[0129] FIG. 9b shows that at 2% BP concentration, the highest amount of grafted PEI is obtained at a 1:1 weight ratio, as expected from the results of Example 5.

[0130] FIG. 9A shows that at 1.0% BP concentration, the highest amount of grafted PEI was obtained at a weight ratio of 3:1.

[0131] FIG. 9C is a 3D bar graph of the grafted PEI fraction for the TGA thermograms of FIGS. 8, 9A and 9B.

[0132] Figure 9C summarizes the amount of grafted PEI for different compositions (BP, SiO2, PEI). The better the concentration, the higher the grafted PEI content.

[0133] These results suggest that the steric hindrance due to the high branching of PEI 25K prevents the possibility of grafting more PEI onto the surface of silica. Based on these results, the maximum amount of grafted PEI 25000 MW appears to be about 30%.

[0134] Example 7: Effect of initiator amount on TGA with low MW PEI To determine the effect of initiator amount, two different percentages of BP were tried at two SI:PEI weight ratios using PEI of MW 600.

[0135] FIG. 10 shows the TGA thermograms (wt % as a function of temperature) of PEI 600MW-based samples for a silica:PEI weight ratio of 1:3 for three different BP concentrations after xylene extraction.

[0136] The amount of PEI grafted onto the silica surface for the three samples did not vary significantly: for 2% BP, about 11% was grafted (top line, SC600-06), for 0.5% BP, about 11% was grafted (middle line, SC600-09), and for 1% BP, about 12% was grafted (bottom line, SC600-03).

[0137] These results, together with those of the previous examples, suggest that it is possible to control and regulate the amount of grafted PEI.

[0138] Example 8: Interaction between PEI MW and BP content To further explore the relative effects of PEI MW and BP initiator concentration, additional experiments were performed.

[0139] 11A and 11B show TGA thermograms (wt % as a function of temperature) of nanocomposites based on PEI 10000MW (FIG. 11A) and PEI 25000MW (FIG. 11A) with a 3:1 weight ratio for three different BP concentrations: 0.5% (green line), 1.0% (orange line), and 2.0% (blue line) after xylene extraction.

[0140] Only one transition was observed for each sample, which means that the grafting reaction was successful no matter what BP initiator concentration was used.

[0141] As shown in Figure 11A, the nanocomposite made with 2% BP underwent the highest weight loss, indicating that 18.81% of PEI was grafted. Interestingly, 0.5% BP produced nearly the same grafting percentage (18.58%). 1% BP produced a significantly lower percentage of grafted PEI (11.09%).

[0142] Figure 11B shows that the lowest percentage of grafted PEI (15.17%) was also obtained for 1.0% BP when the MW of PEI was 25000. However, for PEI MW 25000, the trend is reversed at BP concentrations of 0.5% and 2%. The highest PEI grafting percentage (21.7%) occurred at 0.5% BP. The PEI grafting percentage for 2% BP was 19.57%.

[0143] These results suggest that increasing BP concentration does not contribute significantly to the PEI grafting percentage. PEI 25,000MW consistently showed a higher PEI grafting percentage fraction than PEI 10,000MW. This may be due to the increased branching in PEI 25,000MW, which allows a greater number of nitrogen atoms to bond to the oxygen atoms of silica.

[0144] Based on the cumulative results of Examples 2-8, SC25-0 (Aeorosil 200 nanoparticles, 25,000 MW PEI, 0.5% BP, silica, PEO (3:1)) was selected for further study. This SI / PEI nanocomposite exhibits the highest percentage of grafted PEI (22%) for both the lowest BP concentration and weight ratio. These factors make it a cost-effective option for its industrial use.

[0145] Example 9: Effect of initiator percentage at 1:1 weight ratio Another experiment was carried out to investigate the effect of the percentage of BP initiator in a 1:1 weight ratio.

[0146] Figure 12 shows TGA thermograms (wt % as a function of temperature) of Si / PEI nanocomposite materials based on PEI 25,000 MW with a weight ratio of 1:1 for 0.5% BP (bottom line, SC25-08), 1.0% BP (top line, SC25-02), and 2.0% BP (middle line, SC25-05) concentrations. The same trends as seen in Figure 11B are observed.

[0147] The highest percentage of grafted PEI occurred at 0.5% BP concentration (29.5%) and the lowest percentage of grafted PEI occurred at 1.0% BP concentration (12.8%). Interestingly, at 2.0% BP concentration, the percentage of grafted PEI was approximately 29% relative to the 0.5% BP sample.

[0148] These results confirm that 0.5% BP is sufficient to achieve a high grafting percentage of PEI.

[0149] Example 10: Multivariate Experiments Additional experiments were performed to confirm the results of Example 9 under different conditions.

[0150] 10A, 10B, 10C and 10D show the effect of PEI molecular weight on TGA thermograms for different BP concentrations and weight ratios.

[0151] The data show that the most branched PEI (i.e., highest MW) results in the highest percentage of grafted PEI, regardless of other parameters. Conversely, the lower MW PEI (i.e., 600 and 800) results in lower percentages of grafted PEI, regardless of peroxide concentration and / or silica:PEI weight ratio.

[0152] As shown in Figure 13A, samples SC600-06 and SC800-06 show a lower percentage of grafted PEI, about 10.7% and about 11.3%, respectively, which should ensure an excess of PEI, even though the weight ratio is 1:3. Steric hindrance may also occur with low MW PEI.

[0153] Figure 13B shows a similar trend: Sample SC25-09 shows a low percentage of grafted PEI (11.4%) at a weight ratio of 1:3, despite the PEI MW of 25,000.

[0154] However, when the weight ratio of Si:PEI is 1:1, the percentage of grafted PEI increases significantly with increasing MW.

[0155] FIG. 13C shows that about three times as much PEI was grafted with PEI 25,000 MW compared to PEI 800 MW at a 1:1 weight ratio.

[0156] FIG. 13D shows that there is a clear increase in the grafted fraction when the MW increases from 10K to 25K, with a difference of about 5% at a weight ratio of 1:1.

[0157] In summary, these results suggest that a way to achieve a higher PEI grafting percentage is to use a high MW PEI at a low SI:PEI weight ratio.

[0158] Example 11: Alternating nanoparticle cores Additional experiments were performed using different nanoparticles to investigate the possibility of grafting PEI to other substrates.

[0159] As shown at the end of Example 8, SC25-07 was selected for further study.

[0160] As shown in Figures 14A and 14B and Table 2, the AEROSIL 200 hydrophilic nanoparticles (second line from the bottom) were replaced with three other different types of nanoparticles: hydrophobic fumed silica (AEROSIL R972, top line), methacrylic fumed silica (AEROSIL R711, bottom line), and alumina oxide (Aeroxyde Alu C, second line from the top). All other parameters are the same as those of SC25-07. Figures 14A and 14B show that this process works well for different materials with different surface chemistries. These results support the notion that the proposed PEI grafting is broadly applicable to various types of nanoparticles.

[0161] Table 2. Preparation of nanocomposite materials based on benzoyl peroxide (BP) and various types of NPs, *XX refers to PEI MW (600 for 10,000, 800, 10, and 25 for 25,000 g / mol). [Table 2]

[0162] FIG. 15A shows the FTIR spectra (absorbance as a function of wavenumber / cm) of PEI / Si nanocomposite materials of the three types of nanoparticles in FIGS. 14A and 14B: hydrophobic fumed silica (AEROSIL R972, gray line), methacrylic fumed silica (AEROSIL R711, orange line), and alumina oxide (Aeroxide Alu C, blue line).

[0163] FIG. 15B is a bar graph showing the % weight loss of PEI nanocomposite particles according to various exemplary embodiments of the present invention based on different types of particles.

[0164] This example shows that the specific nanoparticles associated with a given amount of PEI can vary depending on the end use, allowing a specific formulation to be custom tailored for each application, and allowing the user to select the most valuable particles.

[0165] Example 12: Characterization by SEM Characterization by SEM (scanning electron microscopy) was performed to compare the morphology of the grafted PEI with a reference system and to study the dispersion and binding of PEI to the nanoparticles.

[0166] FIG. 16 (16A, 16B, 16C, and 16D) are a series of SEM micrographs.

[0167] FIG. 16A shows AEROSIL 200 silica nanoparticles without PEI.

[0168] FIG. 16B shows PEI 25,000 MW without nanoparticles.

[0169] FIG. 16C shows a mixture of AEROSIL 200 silica nanoparticles and PEI 25,000 MW without the BP initiator.

[0170] FIG. 16D shows sample SC25-07 before xylene extraction.

[0171] As can be seen in Figure 16a, the AEROSIL 200 silica nanoparticles are uniform in size and spherical in shape, which is consistent with the characteristics provided by the manufacturer. Furthermore, little aggregation was observed, as the samples were subjected to ultrasonic treatment before deposition.

[0172] As seen in Figure 16B, PEI 25,000 WM still shows observable roughness even after the nanoparticles are physically added (Figure 16C). In Figure 16C, the silica appears to be located on the surface of the PEI, resulting in aggregation. The mixture in Figure 13B does not contain initiator, so no grafting occurs.

[0173] Figure 16D shows that after the grafting reaction, the roughness of PEI 25,000K MW was reduced to a relatively smooth surface, suggesting that the grafted PEI was well dispersed within the free PEI and acted like a surfactant.

[0174] Figures 17A and 17B are SEM micrographs of SC25-07 nanocomposite particles similar to Figure 16D at higher magnification. The good dispersion of nanoparticles in free PEI further supports the added value of grafted NPs, instead of physical dispersion without chemical bonds. These images further confirm the formation of new chemical bonds. The hydroxyl groups present on the silica surface reacted successfully with the amino groups of PEI. It is known that at acidic and neutral pH, the amino groups of PEI are protonated. The pH of the toluene solution of SC25-07 is 7. The extended morphology of the chains observed in Figures 17A and 17B may be due to electrostatic repulsion between different groups of PEI.

[0175] Some aggregation is also observed, which may be the result of aggregation of ungrafted PEI chains and / or nanoparticles.

[0176] Overall, this example shows that grafting is important to finely disperse the nanoparticles within the matrix. As the nanoparticles are dispersed, their surface area increases, and therefore the area for adsorption increases. In some embodiments, the increased area for adsorption contributes to a faster increase in the rate of adsorption of VOCs and / or an increase in the amount of VOCs adsorbed.

[0177] Example 13: PEI grafted onto nanoparticles reduces release from polymeric materials To evaluate the potential of PEI nanocomposite particles according to exemplary embodiments of the present invention to reduce emissions from polymeric materials, they were compared to a commercially available odor-reducing additive.

[0178] Figure 18 is a bar graph showing the total emissions in PPM as measured by GCMS. Measurements were taken after 30 minutes at 90°C and 60 minutes at 120°C. The test material was recycled PVC with added blowing agent.

[0179] In Figure 18, R indicates an untreated reference sample containing only the test material (polyvinyl chloride (PVC) with an azo blowing agent); C represents a positive control sample with 0.5% of a commercial odor-reducing additive plus test material; E shows an experimental sample having 0.5% PEI nanocomposite particles according to an exemplary embodiment of the present invention.

[0180] This example shows that PEI nanocomposite particles according to illustrative embodiments are more effective than commercial products in reducing release from PVC under the assay conditions shown.

[0181] Example 14: PEI grafted onto nanoparticles reduces odor To confirm the results of the previous examples, additional experiments were performed using G1 polymer (Plastofil, Israel). 30% recycled material was mixed with 70% G1 pellets with or without odor-reducing additive and extruded. A panel of five human volunteers smelled each sample and rated it on a scale of 0 (no perceptible odor) to 5 (very strong odor). The odor-reducing additives were 2% commercial odor-reducing additive, 0.25% ungrafted PEI, and 0.25% PEI nanocomposite particles according to an exemplary embodiment of the present invention (0.25% SC-07 25).

[0182] FIG. 19 shows that 0.25% PEI nanocomposite particles according to an exemplary embodiment of the present invention reduce odor more than 2% of a commercial odor reducing product and also reduce odor more than PEI alone.

[0183] This example demonstrates that grafting PEI onto a nanoparticle substrate increases its effectiveness in reducing odor emanating from polymeric materials.

[0184] Example 15: Graphical summary To facilitate a better understanding of the data presented in Examples 22-10, the data are summarized graphically.

[0185] FIG. 20 is a bar graph illustrating the % weight loss as a function of PB concentration (%) of PEI 25,000 MW nanocomposite particles having different SI:PEI weight ratios according to various exemplary embodiments of the present invention.

[0186] FIG. 21 is a bar graph showing the % weight loss as a function of PB concentration (%) of PEI 10,000 MW nanocomposite particles having different SI:PEI weight ratios according to various exemplary embodiments of the present invention.

[0187] FIG. 22 is a bar graph showing the % weight loss as a function of PB concentration (%) of PEI 800 MW nanocomposite particles having different SI:PEI weight ratios according to various exemplary embodiments of the present invention.

[0188] These graphical summaries reveal that the grafting reaction occurs after optimization at different parameters, and the SC-07-25 composition was selected as the most promising one because it has the highest grafted PEI with minimal reagents used (i.e., it is less expensive than the others).

[0189] Example 16: Exemplary scale-up The above description relates primarily to laboratory scale procedures. To move to industrial production, a limited scale-up has been performed and is described in detail herein, which should provide sufficient guidance for industrial process specialists to further scale up the process.

[0190] A 100 L vessel was placed in a cooling bath. The desired amount of nanoparticles (e.g. AEROSIL 200) was added in ethanol 99.9% at a volume ratio of 1% kg / liter and the cooling system was turned on.

[0191] The nanoparticles were dispersed by sonication for at least 2 hours at 50% amplitude with a 4500W sonicator at 15 minute intervals.

[0192] PEI 25000 MW was pre-dissolved in 1 L of ethanol and sonicated for 15 min (3 intervals of 5 min and 25% amplitude) using a 750 W sonicator. Pre-dissolution can be reduced or eliminated with lower MW PEI sonication due to its lower viscosity.

[0193] The pre-dissolved PEI 25000 MW solution and the desired amount of recrystallized BP were added to the silica dispersion (in a 100 L vessel). The nanoparticles, PEI and BP were sonicated together for at least 1 h at 50% amplitude with 15 min intervals using a 4500 W sonicator.

[0194] The resulting solution was pumped into another vessel and the reaction was allowed to complete for 24 hours. The reaction mixture was filtered using a vacuum filter funnel to produce a filter cake. The filter cake was collected and dried overnight in a vacuum oven at 60° C. In some embodiments, further ethanol washing and / or xylene extraction are performed as described herein above.

[0195] The following table provides exemplary reagent amounts: Table 3: Exemplary SI / PEI nanocomposite recipes. [Table 3] Table 4: Additional exemplary SI / PEI nanocomposite recipes [Table 4] Table 5: Additional exemplary SI / PEI nanocomposite recipes [Table 5]

[0196] Example 17: PEI grafted onto carbon black nanoparticles To demonstrate that the above grafting PEI method is applicable to a wide range of nanoparticle types, additional experiments were performed using EC300 carbon black nanoparticles and PEI25,000MW or PEI25,000MW as reference standards. A nanoparticle to PEI weight ratio of 3:1 was used.

[0197] The results are summarized graphically in Figures 23A and 23B, which present TGA thermograms, and Figures 23C and 23D, which present DTG thermograms.

[0198] 23A and 23C show the results of nanocomposite particles according to an exemplary embodiment of the present invention, in which EC300 carbon black nanoparticles are grafted to PEI 25,000 MW after xylene extraction.

[0199] Figures 23B and 23D show the results for PEI 25,000 MW as the reference standard.

[0200] These results demonstrate that PEI is grafted to the carbonaceous particles. In this experiment, the grafting percentage was calculated as 14% or 56% of the PEI initially added to the reaction.

[0201] Compared with previous Examples 5 and 6, these results suggest that the grafting of PEI to carbon black is slightly less than that of silica particles, however, the use of carbonaceous particles may broaden the range of odorants that can be suppressed.

[0202] Example 18: PEI grafted onto carbon nanotube nanoparticles To demonstrate that the above grafting PEI method is applicable to a wide range of nanoparticle types, additional experiments were performed using SW07 carbon nanotube nanoparticles and PEI 25,000 MW or SW07 carbon nanotube nanoparticles without PEI as reference standards. A nanoparticle to PEI weight ratio of 3:1 was used.

[0203] The results are summarized graphically in Figures 24A and 24B, which present TGA thermograms, and Figures 24C and 24D, which present DTG thermograms.

[0204] 24A and 24C show the results of nanocomposite particles according to an exemplary embodiment of the present invention, in which SW07 carbon nanotube nanoparticles are grafted to PEI 25,000 MW after xylene extraction.

[0205] Figures 24B and 24D show the results for SW07 carbon nanotube nanoparticles without PEI as a reference standard.

[0206] These results demonstrate that PEI is grafted to carbon nanotube particles. In this experiment, the grafting percentage was calculated as 21% or 84% of the PEI initially added to the reaction.

[0207] Compared with previous Examples 5 and 6, these results suggest that the grafting of PEI to the carbon nanotubes was slightly more than that to the silica particles. Again, the use of carbon nanotube particles may broaden the range of odorants that can be suppressed.

Claims

1. (a) adding at least 5% poly(ethyleneimine) (PEI) on a w / w basis to nanoparticles dispersed in an organic solvent; (b) adding at least 0.1% benzoyl peroxide (BP) on a w / w basis to said nanoparticles; (c) sonicating; A method comprising:

2. 10. The method of claim 1, wherein the nanoparticles comprise one of fumed silica, methacrylic silica, aluminum oxide (Al2O3), ZnO, zeolite, TiO2, carbon nanotubes, graphene, and carbon black.

3. 10. The method of claim 1, further comprising at least one of the steps of adding at least 30% PEI to the nanoparticles, adding at least 100% PEI to the nanoparticles, adding at least 1% BP to the nanoparticles, and adding at least 2% BP to the nanoparticles.

4. (a) premixing PEI coated nanoparticles with a polymeric material to form a premix; (b) mixing additional polymeric material with the premix to form a final mixture; (c) extruding the final mixture; A method comprising:

5. The method of claim 4 , wherein the polymeric material and / or the additional polymeric material is recycled.

6. The method of claim 4 including the step of adding a filler during said mixing.

7. The method of claim 4 including the step of adding a filler during said extrusion.

8. 5. The method of claim 4, wherein the polymeric material and the additional polymeric material each independently comprise at least one material selected from the group consisting of polyvinyl chloride (PVC), polyethylene (PE, LDPE, HDPE, PEX), polypropylene (PP), polycarbonate (PC), polyamide (PA), polyacrylate, polymethacrylate (PAM), polystyrene (PS), ethylene vinyl alcohol (EVOH), ethylene vinyl acetate (EVA), isoprene, styrene-isoprene-styrene (SIS) block copolymer, butadiene, acrylonitrile butadiene styrene (ABS).

9. The method of claim 4, wherein the final mixture comprises at least 0.01% (w / w) of PEI coated nanoparticles.

10. 5. The method of claim 4, wherein the final mixture contains up to 25% (w / w) of PEI coated nanoparticles.

11. 5. An article produced by the method of claim 4.

12. (a) dispersing PEI coated nanoparticles in a liquid medium to form a suspension; (b) applying the suspension to a surface of an article; (c) evaporating the liquid medium; A method comprising:

13. The method of claim 12 comprising gelling the liquid medium.

14. The method of claim 12 , wherein the liquid medium comprises water.

15. The method of claim 12 , wherein the liquid medium comprises an organic solvent.

16. 16. The method of claim 15, wherein the organic solvent comprises ethanol.

17. The nanoparticles coated with PEI are silica nanoparticles, methacrylic silica nanoparticles, aluminum oxide (Al 2 O 3 ) nanoparticles, ZnO nanoparticles, zeolite nanoparticles, TiO 2 13. The method of claim 12, comprising at least one member selected from the group consisting of nanoparticles, carbon nanotube nanoparticles, and graphene nanoparticles.

18. The method of claim 12, wherein the PEI-coated nanoparticles are present in the liquid medium at a concentration of at least 0.01% W / V.

19. 13. The method of claim 12, wherein the applying step comprises at least one action selected from the group consisting of spraying, brushing, doping, rolling, smear coating, and dipping.

20. 13. The method of claim 12, wherein the product comprises at least one material selected from the group consisting of polyvinyl chloride (PVC), polyethylene (PE, LDPE, HDPE, PEX), polypropylene (PP), polycarbonate (PC), polyamide (PA), polyacrylate, polymethacrylate (PAM), polystyrene (PS), high density polystyrene (HIPS), ethylene vinyl alcohol (EVOH), ethylene vinyl acetate (EVA), isoprene, styrene-isoprene-styrene (SIS) block copolymer, butadiene, acrylonitrile butadiene styrene (ABS).